Financial Literacy Education with an Aboriginal Community: Identifying Critical Moments for Enabling Praxis - Levon Ellen Blue (Education Sciences, 2019)
Conventional financial literacy education (FLE) practices promote individual choice and responsibility for financial circumstances. The untruth connected to conventional FLE is that achieving financial well-being is possible after acquiring financial skills and knowledge and choosing to make effective financial decisions. In this article, I share an exploration of FLE practices with an Aboriginal community that unfolded after a conventional train-the-trainer financial literacy workshop failed to gain traction. Nineteen semi-structured interviews took place with community members to understand their experiences, interest and perceived relevance of FLE. The importance of site-specific FLE was revealed as the tension between individual wealth accumulation practices promoted in conventional FLE collided with Indigenous ways of being, knowing and doing. Identified are critical moments for reflection that may enable praxis in FLE. By enabling praxis an educator moves away from conventional one-size-fits-all approaches to FLE, where participants’ needs are assumed, and towards more tailored approaches.